PEMANFAATAN OBJEK WISATA MAKAM RAJA SIDABUTAR SEBAGAI WISATA BUDAYA DI SAMOSIR, SUMATERA UTARA - Simorangkir, Victricia (Humanis, 2015)
Tourism Object is a charm sourced in cultural objects. One of the example, the Area in the Village Tombs of the Kings Sidabutar Tomok Samosir regency, North Suamtera Province has the remains of human things of the past to do research on utilization. This study aims to examine 1) the potential of the Area Tomb of King Sidabutar and 2) Efforts to use the royal cemetery at Sidabutar attraction as a cultural tourism. In an effort to answer the problems in this study namely the potential and capacity utilization of the Tomb of King Sidabutar area, then used data collection techniques based on observation, interview, kuisioner, and library studies. Once that is done processing the data that is derived using qualitative and contextual analysis. The theory also used in this study to answer the problem is using the theory of management. Based on the analysis conducted, utilization Tourism Tombs of the Kings Sidabutar as cultural tourism, acquired 1) the development potential that is the potential of cultural and nonarkeologis potential. Potential culture include: three sarcophagus (tomb), a small sarcophagus, stone statue, statues sigale-gale, Sidabutar village, tung-tung, and Batak Museum and nonarkeologis potential that is Lake Toba and Ritual Pasiarhon. Capacity utilization is done in addition to the religious importance of the importance of tourism need the protection, development, and conservation.
Keywords: utilization, the Tomb of King Sidabutar area, cultural tourism